Integration problems of regional authorities of technical regulation and inspections on consumer protection - Куликова, Ольга Николаевна; Маматов, Валерий Петрович (Technology audit and production reserves, 2014)
The problems of improving the activity of territorial authorities on the state consumer policy implementation were considered since the quality of this activity is the determining factor for stable regional development. State control has a great effect on the functions of other organizations. Their broad "punitive" powers are still not considered as service activities; therefore, the change in the work of these bodies must be paramount to accelerate the European integration process. Assessment of possible integration spheres of territorial authorities of technical regulation and inspections on consumer protection to perform their basic powers effectively was conducted. To improve the implementation effectiveness of state policy on consumer protection, it is proposed to combine the potential of regional inspections on consumer protection and state centers of standardization, metrology and certification into the territorial bodies of the State Inspection of Ukraine for Consumer Rights Protection - Head Offices of the State Inspection for Consumer Rights Protection in the administrative centers of Ukraine.